2020
DOI: 10.1136/bmjopen-2019-035416
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate plus metformin for fertility-sparing treatment of atypical endometrial hyperplasia and endometrial carcinoma: trial protocol for a prospective, randomised, open, blinded-endpoint design, dose-response trial (FELICIA trial)

Abstract: IntroductionProgestin therapy is the only fertility-sparing treatment option for patients with atypical endometrial hyperplasia (AEH) and endometrial cancer (EC). However, the results of three meta-analyses revealed a high remission rate, as well as an association with a high rate of relapse. We previously conducted a phase II of medroxyprogesterone acetate (MPA) plus metformin as a fertility-sparing treatment for AEH and EC patients, and reported that metformin inhibited disease relapse after remission.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Silencing of TICRR and PPIF led to enhance the expression of epithelial marker E-cadherin and decrease the mesenchymal marker N-cadherin and metastasis associated genes MMP9 as well as proliferation-related marker CCND1, suggesting their involvement in the progression of endometrial cancer ( Figure 6E ). Medroxyprogesterone acetate (MPA) as a conservative therapy is commonly applied to the early stage of endometrial carcinoma [ 19 ]. The knockdown of TICRR resulted in a potent decrease of cell growth and clone formation and enhanced the inhibitory effect of MPA ( Figure 6F ) and the downregulated PPIF yielded the similar results ( Figure 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…Silencing of TICRR and PPIF led to enhance the expression of epithelial marker E-cadherin and decrease the mesenchymal marker N-cadherin and metastasis associated genes MMP9 as well as proliferation-related marker CCND1, suggesting their involvement in the progression of endometrial cancer ( Figure 6E ). Medroxyprogesterone acetate (MPA) as a conservative therapy is commonly applied to the early stage of endometrial carcinoma [ 19 ]. The knockdown of TICRR resulted in a potent decrease of cell growth and clone formation and enhanced the inhibitory effect of MPA ( Figure 6F ) and the downregulated PPIF yielded the similar results ( Figure 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it was found, that only pretreatment BMI !25 kg/m 2 , not the change in BMI during the treatment is a significant factor in achieving the complete response [11]. The overall effects of metformin on oncological and obstetrical outcomes are planned to be examined in randomized study [35].…”
Section: Discussionmentioning
confidence: 99%
“…The dosage forms of gestagens existing in the Russian pharmaceutical market and indications for their use are presented in the Table. Gestagens are successfully used for contraception, pregnancy maintenance, and secondary amenorrhea. They are the front-line therapy for endometrial hyperplasia and cancer [18][19][20]. Gestagens are used in hormone replacement therapy (HRT) to prevent osteoporosis and in ART procedures [21].…”
Section: Clinical Use Of Gestagensmentioning
confidence: 99%
“…Metformin is a biguanide widely used in the treatment of type 2 diabetes. Analysis of several recent epidemiological studies [ 19 , 69 , 70 ] has shown that metformin reduces the risk of cancer development and mortality in diabetic patients with endometrial hyperplasia and carcinoma.…”
Section: Clinical Use Of Gestagensmentioning
confidence: 99%